The Brazilian plan to create a Digital Communications Service (Law, State and Telecommunications Review, 2013)
Purpose ”“ This update analyses the proposal for the regulation and universalization of broadband through a new service named Digital Communications Service (SCD), which did not prosper in the National Telecommunications Agency (ANATEL) of Brazil.Methodology/approach/design ”“ The research describes the regulatory scenario of telecommunications in 2003 in Brazil and the reasoning of creating a new category of service named Digital Communications Service (SCD) in accord with contemporary demands for telecommunications universalization in Brazil.Findings ”“ Political and juridical support for the creation of a new category of telecommunications services named Digital Communications Service (SCD) was weakened after other venues were open to reach the SCD goals through incentives directed to the deployment of the Fixed Switched Telephone Service (STFC) infrastructure (backhaul) and the perspective of use of the Universalization Fund by enacting new legislation on the matter.Practical implications ”“ This update enlightens the actual effects of regulatory reasoning through an emblematic case analysis of a failure proposal to create a new service category designed to fulfill universalization demands on broadband in Brazil.